A Feasibility Study the Effectiveness of Self-care Promoting Program on Self-care Behavioral and Clinical Outcomes in People with Corneal Transplantation: A Quasi-experiment Study - Tupcharoen, Kanokon; Phinitkhajorndech, Noppawan; Puangsricharern,Vilavun (Pacific Rim International Journal of Nursing Research, 2024)
Corneal transplantation is the most effective treatment for visual impairment caused by corneal blindness and can improve patients’ quality of vision. However, pre- and post-operative self-care is necessary to reduce the risk of complications and graft rejection. This one-group, quasi-experimental design with repeated measures aimed to determine the feasibility and effectiveness of self-care promoting programs on self-care behavior, anxiety, and clinical outcomes in individuals with corneal transplantation. Thirty participants who met the inclusion criteria were purposively recruited from a corneal excellence center in Bangkok, Thailand, from October 2021 to August 2022. The data collection instruments included the Demographic and Health Data Forms, the Self-Care Behavior Questionnaire, and the Self-Rating Anxiety Scale. The data were analyzed using descriptive statistics, paired t-tests, and Friedman and Wilcoxon signed-rank tests. The program was found to be feasible, with all participants able to attend for 30 days postoperation. In terms of effectiveness, participants demonstrated improved self-care behavior and reduced anxiety compared to pre-program levels. Visual acuity also showed improvement 30 days postoperation, with 83.3% of participants having a clear corneal graft. These findings are significant for nursing practice, as they suggest that this program could be a promising tool for enhancing self-care behavior in individuals undergoing corneal transplantation. Nurses could potentially use this program to promote self-care behavior, alleviate anxiety, and enhance clinical outcomes. However, further research with randomized control is necessary before widespread implementation can be recommended.